2000
DOI: 10.1101/lm.7.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent Differences in LTP and Hippocampus-dependent Memory in Inbred Mice

Abstract: Many studies have used "reverse" genetics to produce "knock-out" and transgenic mice to explore the roles of various molecules in long-term potentiation (LTP) and spatial memory. The existence of a variety of inbred strains of mice provides an additional way of exploring the genetic bases of learning and memory. We examined behavioral memory and LTP expression in area CA1 of hippocampal slices prepared from four different inbred strains of mice: C57BL/6J, CBA/J, DBA/2J, and 129/SvEms-+ Ter? /J. We found that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
208
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(237 citation statements)
references
References 48 publications
21
208
8
Order By: Relevance
“…C57BL/6 mice are known to perform well in hippocampal-dependent behavioral tasks, including T-maze spontaneous alternation (Gerlai, 1998a) and context-dependent fear condi-tioning (Gerlai, 1998b;Paylor et al, 1994). These mice also exhibit excellent hippocampal long-term potentiation measured ex vivo (Nguyen et al, 2000a) or in vivo (Matsuyama et al, 1997). Using this strain, Gerlai et al (1999) demonstrated impaired acquisition of memory in a hippocampal-dependent manner in response to intrahippocampal infusion of a genetically engineered antibody-like protein, an immunoadhesin, that selectively antagonized EphA function (Gerlai et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…C57BL/6 mice are known to perform well in hippocampal-dependent behavioral tasks, including T-maze spontaneous alternation (Gerlai, 1998a) and context-dependent fear condi-tioning (Gerlai, 1998b;Paylor et al, 1994). These mice also exhibit excellent hippocampal long-term potentiation measured ex vivo (Nguyen et al, 2000a) or in vivo (Matsuyama et al, 1997). Using this strain, Gerlai et al (1999) demonstrated impaired acquisition of memory in a hippocampal-dependent manner in response to intrahippocampal infusion of a genetically engineered antibody-like protein, an immunoadhesin, that selectively antagonized EphA function (Gerlai et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The authors explained that "the intention is usually to demonstrate a link between neuronal function and behavior." To work toward this goal, Nguyen et al (2000a) analyzed both the behavioral and synaptic function of four inbred mouse strains: C57BL/6J, CBA/J, DBA/2J, and 129 SvEmsϩ ter /J. These investigators found genotype-dependent differences in LTP and in learning performance between the strains.…”
Section: Inbred Strains: Characterization Of Synaptic Plasticity and mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the existence of variation in learning abilities among individuals belonging to the same species has been recognized for a long time (James 1890;Habib et al 2000;Nguyen et al 2000), the neurobiological correlates underlying such variability are largely unknown. In humans, imaging studies have shown different patterns of brain activation to be associated with different levels of learning and memory performance (Habib et al 2000;Cazalis et al 2003).…”
mentioning
confidence: 99%